Active Precipitation of Radiation Belt Electrons Using Rocket Exhaust Driven Amplification (REDA) of Man‐Made Whistlers. Issue 6 (1st June 2022) - Bernhardt, P. A.; Hua, M.; Bortnik, J.; Ma, Q.; Verronen, P. T.; McCarthy, M. P.; Hampton, D. L.; Golkowski, M.; Cohen, M. B.; Richardson, D. K.; Howarth, A. D.; James, H. G.; et al.
Abstract: Ground‐based very low frequency (VLF) transmitters located around the world generate signals that leak through the bottom side of the ionosphere in the form of whistler mode waves. Wave and particle measurements on satellites have observed that these man‐made VLF waves can be strong enough to scatter trapped energetic electrons into low pitch angle orbits, causing loss by absorption in the lower atmosphere. This precipitation loss process is greatly enhanced by intentional amplification of the whistler waves using a newly discovered process called rocket exhaust driven amplification (REDA). Satellite measurements of REDA have shown between 30 and 50 dB intensification of VLF waves in space using a 60 s burn of the 150 g/s thruster on the Cygnus satellite that services the International Space Station. This controlled amplification process is adequate to deplete the energetic particle population on the affected field lines in a few minutes rather than the multi‐day period it would take naturally. Numerical simulations of the pitch angle diffusion for radiation belt particles use the UCLA quasi‐linear Fokker Planck model to assess the impact of REDA on radiation belt remediation of newly injected energetic electrons. The simulated precipitation fluxes of energetic electrons are applied to models of D‐region electron density and bremsstrahlung X‐rays for predictions of the modified environment that can be observed with satellite and ground‐based sensors. Plain Language Summary: The Earth's radiation belts respond to whistler waves by changes in electron particle orbits. The amount of particle pitch angle deflection depends on the strength of the wave electric field of the propagating electromagnetic wave. Current sources of whistlers from both ground and satellite sources have amplitudes less than about 10 pT. A new technique that can greatly increase this amplitude is called rocket exhaust driven amplification (REDA). Experimental measurements of REDA show between 30 and 50 dB enhancements in the power of the whistlers. These enhancements are sufficient to rapidly reduce the energetic electron population on affected field lines in the radiation belts in minutes which would take days with unamplified whistler waves. During the radiation belt remediation process, energetic electrons are precipitated into the lower atmosphere where enhanced optical emissions, D‐region absorption galactic radio signals, and X‐ray emissions can provide a measure of the REDA effeteness. Key Points: Rocket exhaust driven amplification (REDA) produces the strongest whistler amplitudes measured in space from ground‐based very low frequency (VLF) transmitters REDA intensified whistlers can rapidly scatter radiation belt electrons into the loss cone in minutes rather than days Effects of REDA induced electron losses to the atmosphere include enhanced X‐rays, airglow, VLF propagation changes, and radio absorption